Role of s-nitrosoglutathione reductase and nucleoredoxins in redox-mediated plant defence - Keyani, Rumana (The University of Edinburgh, 2014)
Redox reactions are an essential part of the cell’s metabolism, differentiation, and responses to the prevailing environmental conditions. In plants, dramatic changes in cellular redox status are observed upon exposure to environmental stresses, including pathogen attack. These changes affect the oxidative status of reactive cysteine thiols in regulatory proteins. To control oxidative protein modifications, plant cells employ the antioxidant enzymes S-nitrosoglutathione Reductase 1 (GSNOR1) and members of the Thioredoxin (TRX) superfamily. Immune signalling by the hormone salicylic acid (SA) is particularly dependent on the activity of these enzymes. SA is synthesized in response to challenge by plant pathogens for the establishment of local and systemic immunity. SA accumulation is regulated by cellular levels of S-nitrosoglutathione (GSNO), a redox molecule capable of S-nitrosylating proteins (i.e., covalent attachment of nitric oxide to cysteines). GSNOR1 is thought to regulate cellular GSNO and global S-nitrosylation levels, but it is unknown how GSNOR1 regulates SA biosynthesis. Furthermore, SA recruits the activities of selected TRX enzymes that act as ubiquitous thiol reductases to counteract cysteine oxidation of SA-responsive regulatory proteins, thereby modulating their activities. However, it is unclear how SA controls nuclear redox processes involved in SAresponsive gene activation. Here we show that GSNOR1 regulates SA accumulation by regulating the expression of SA biosynthetic genes and their transcriptional activators. Moreover, we describe Nucleoredoxins (NRX) that represent novel, potentially nuclear localized members of the TRX superfamily. Mutant nrx1 plants displayed enhanced disease resistance, which was associated with enhanced expression of genes involved in synthesis of salicylic acid. Unlike classical TRX, NRX enzymes contain multiple active sites, suggesting they may exhibit significant reductase or remodelling activities. Indeed, insulin turbidity assays indicated that NRX proteins show an unusual form of disulphide reduction activity. Taken together, the data presented in this thesis demonstrate that GSNOR1 and NRX enzymes play critical roles in regulating synthesis of and signalling by SA in plant immunity.
Keywords: redox enzymes; redox mediated; plant defence